2022
DOI: 10.1002/ange.202213433
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Covalent Michael Acceptors to Penetrate Cells: Thiol‐Mediated Uptake with Tetrel‐Centered Exchange Cascades, Assisted by Halogen‐Bonding Switches

Abstract: Chalcogen-centered cascade exchange chemistry is increasingly understood to account for thiol-mediated uptake, that is, the ability of reversibly thiol-reactive agents to penetrate cells. Here, reversible Michael acceptors are shown to enable and inhibit thiolmediated uptake, including the cytosolic delivery of proteins. Dynamic cyano-cinnamate dimers rival the best chalcogen-centered inhibitors. Patterns generated in inhibition heatmaps reveal contributions from halogen-bonding switches that occur independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 76 publications
(86 reference statements)
2
12
0
Order By: Relevance
“…This inhibition was three times weaker than the dimeric Michael acceptor 1 and also weaker than the locked thioacetal control 8 with 9±1 μ m . This result thus confirmed that exchange with the central disulfide bridge is negligible for activity and implied that the halogen‐bond switches identified with Michael acceptor monomers [26] also operate on the dimer level ( Figure 2 ,a ). Namely, para trifluoromethyls have a Hammett σ p =0.54 well beyond ketone and aldehyde acceptors with σ p =0.42, not to speak of iodines with σ p =0.18 [86] .…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…This inhibition was three times weaker than the dimeric Michael acceptor 1 and also weaker than the locked thioacetal control 8 with 9±1 μ m . This result thus confirmed that exchange with the central disulfide bridge is negligible for activity and implied that the halogen‐bond switches identified with Michael acceptor monomers [26] also operate on the dimer level ( Figure 2 ,a ). Namely, para trifluoromethyls have a Hammett σ p =0.54 well beyond ketone and aldehyde acceptors with σ p =0.42, not to speak of iodines with σ p =0.18 [86] .…”
Section: Resultssupporting
confidence: 60%
“…The activity of tetrel‐centered CAXs as inhibitors of thiol‐mediated uptake was assessed with fluorescently labeled epidithiodiketopiperazine 9 as a reporter ( Figure 4). This natural product derived CAX provides one of the most active and brightest TMU probes, [79] which has been used extensively to characterize new TMU inhibitors [18,22,26] . Inhibition efficiencies were assessed using automated high‐content high‐throughput imaging microscopy [18,22,26] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations